Cloud Migration Decision Support Model for SMEs - Knettig, Jan; Maryška, Miloš; Janák, Jiří; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
Thesis Cloud Migration Decision Support Model for SMEs is focused on the topic of Cloud Computing, specifically on the cloud adoption potential in Czech SMEs (Small and Middle-sized Enterprises).To simplify the process for SMEs of adopting cloud the aim of this Thesis is to design a Cloud Migration Decision Support Model to help them make the right decision on whether cloud or on-premises solutions are their better fit.In order to create such a Model, large qualitative market research on cloud adoption potential by Czech SMEs managers was conducted in 39 SMEs. This research, containing 27 open-ended questions and producing 1500 short answers, was analyzed and from this came the decision criteria which are further used as inputs to the Model. This was done to assure the correspondence of the Model with the real needs and approaches of SMEs. Apart from that, it also serves as market research bringing a view on the current market situation regarding cloud services and SMEs.The Research showed that 75% of companies asked use some kind of cloud application. More than 60% keep their backups (also) externally and a little less than 50% of companies claim to have a part of their servers located on third party’s premises, suggesting a high cloud adoption rate. On the other hand, many respondents were not able to fully define cloud and often they considered it only a distant data storage. Combined with the facts that ‘private cloud’ could not be correctly defined by 50% of companies, cloud is a synonym of ‘public cloud’ for many companies and that cloud is only used for a fraction of activities in most companies, there is still a great potential for further increasing the cloud adoption rate by increasing the awareness of what cloud computing offers.The created Model contains 7 assessment steps and is elaborated in a form of 7 mind maps, each containing specific assessment criteria which bring its users recommendations on suitable solutions to their needs.
The steps are in this order: Need, Quality, Security, Simplicity, Agility, References and Price. This Model was fully validated by conducting studies with 5 companies. This validation proved the Model’s usability and at the same time it showed its limitations and suggested some future work directions.Prior to creating the Model and conducting the Research, ICT and cloud related theory was studied and described, as well as the theory of qualitative research. An important part of this Thesis is also a detailed description of the design and conducting of the Research, which shall serve as a useful guideline for future researchers in this field.
Vedoucí práce: Miloš Maryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses